Enzymatic alcoholysis of triolein to produce wax ester - Mat Hadzir, Nursyamsyila; Basri, Mahiran; Abd Rahman, Mohd Basyaruddin; Abdul Razak, Che Nyonya; Abd Rahman, Raja Noor Zaliha; Salleh, Abu Bakar (Wiley, 2001)
An alcoholysis reaction between triolein and oleyl alcohol catalyzed by Lipozyme and Novozyme was carried out to produce oleyl oleate, a wax ester. The effects of various reaction parameters such as time, reaction temperature, amount of enzyme, molar ratio of substrates (oleyl alcohol/triolein), various organic solvents used and the initial water activity, aw of the reaction system were studied. The best conditions tested to produce wax ester were respectively, incubation time, 5h; temperature, 50°C for Lipozyme and 60°C for Novozyme; weight of enzyme, 0.30g and molar ratio of oleyl alcohol to triolein, 6:1. The use of organic solvents greatly influenced the activity of lipase. Generally, the activity of lipase was high in nonpolar solvents with log P values greater than 2.50. Heptane and hexane were the best solvents tested. The enzymatic synthesis of oleyl was best carried out at aw 0.32. Analysis of the yield of the products of the reaction at optimized reaction condition using Lipozyme showed that 75.66% oleyl oleate was produced.